(untitled) (International Journal of Engineering and Computer Science, 2014)
Steganography is becoming an important area of research in recent years. It is an art and the science of embedding information into cover image viz., text , video, audio or multimedia content for military communication, authentication and many other purposes. It deals with the ways of hiding the communication message and its existence from the unintended user. In image steganography, secret communication is achieved through embedding a message into an image as cover file and generates a stego-image having hidden information. There are several image steganography techniques are used each have its pros and cons. This paper discusses various image steganography techniques such as Least significant bit, Discrete wavelet transformation, Pixel value differencing, Discrete cosine transformation, Masking and filtering etc.